ANALISIS EMPIRIK MEDIA PEMBELAJARAN FISIKA ANIMASI TIGA DIMENSI MENGGUNAKAN BLENDER PADA MATERI INTI ATOM UNTUK SEKOLAH MENENGAH ATAS - Nasir, Muhammad; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to empirically analyze physics learning media in three-dimensional animation by using Blender application on subject of atomic core for senior high school. This research is the Research and Development type use ADDIEmodel of instructional Design. The subject of this study is the physics learning media in three-dimensional animation using Blender application on subject of atomic core for senior high school. The data in this study is a media assessment score which is given by the respondents through questionnaires. The respondents consisted of 11 teachers of physics (Expert), 20 teachers of physics (Expert User) and 22 students (User) in SMA Pekanbaru. Furthermore, the data were analyzed for validity test through product moment correlation technique and reliability test through Cronbach's alpha technique. Based on data analysis, the value of r count of validity of the assessment score which is given by respondents to the physics learning media is greater than r table. And reliability assessment score which is given by respondents to the physics learning media, has a Cronbach's alpha of greater than 0.7. It can be concluded that the physics learning media in three-dimensional animation using Blender application on subject of atomic core is valid and reliable by teachers and students so that proper used for physics learning media in senior high school.Key Words: Empirical Analysis, Three-Dimensional Animation, Blender Aplication